Thickness Variation Characteristics of Tidal Rhythmites—An Example From the Pinghu Formation, Xihu Sag, East China Sea Shelf Basin - Liu, Siqi; Zhang, Changmin; Zhu, Rui; Li, Jinchi; Wang, Zeyu (Frontiers in Earth Science, 2022)
The Pinghu Formation of the Xihu Sag in the East China Sea shelf basin is influenced by tidal processes, but few studies have focused on its tidal rhythmites. Through detailed observation and description of cores, this article studies the periodicity of the tidal rhythmites of well A-11 by using the grayscale measurement of digital images based on spectral analysis and wavelet transform. According to the statistical data series of millimeter lamination thickness, the sandy lamina thickness, the argillaceous lamina thickness, and the couplet thickness were quantitatively compared and analyzed, to support the interpretation of the main controlling factors of different thickness cycles. The periodicity of sandy laminae, argillaceous laminae, and couplet thickness have distinct differences, which are interpreted to be due to differences in the nature and magnitude of tidal current cycles at the time of deposition. The high-frequency signal represents event deposition, the middle-frequency signal represents tidal current deposition, and the low-frequency signal highlights changes in sedimentary facies. Therefore, the change in the couplet thickness is controlled by event deposition, tidal current deposition, and change of the depositional environment. Our approach to the study of thickness variations in tidal rhythmites supports the reconstruction of the tidal sedimentary environment in the paleostratigraphic sequence.